2006
DOI: 10.3892/or.15.2.443
|View full text |Cite
|
Sign up to set email alerts
|

Promoter CpG methylation of multiple genes in pituitary adenomas: frequent involvement of caspase-8

Abstract: The epigenetic changes in pituitary adenomas were identified by evaluating the methylation status of nine genes (RB1, p14 ARF , p16 INK4a , p73, MGMT, DAPK, in a series of 35 tumours using methylationspecific PCR analysis plus sequencing. The series included non-functional adenomas (n=23), prolactinomas (n=6), prolactinoma plus thyroid-stimulating hormone adenoma (n=1), growth hormone adenomas (n=4), and adrenocorticotropic adenoma (n=1). All of the tumours had methylation of at least one of these genes and 40… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
22
2

Year Published

2007
2007
2017
2017

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(26 citation statements)
references
References 24 publications
2
22
2
Order By: Relevance
“…Interestingly, genes of the RB1 pathway were methylated in 85% of the samples, which suggests that, in addition to MEN1 mutations, methylation could be a molecular alteration that contributes to these tumors. These results were also confirmed by Bello et al (2006), who found promoter hypermethylation in the RB1, P14 (ARF), P16, and P73 genes, as well as the metalloproteinase inhibitor 3 (TIMP3), O-6-methylguanine DNA methyltransferase (MGMT), DAPK (DAPK1), THBS1, and CASP8 genes, some of which are involved in the apoptosis processes (DAPK and CASP8), DNA repair (MGMT) or have anti-angiogenic properties (THBS1). Additionally, reduced expression of the fibroblast growth factor receptor (FGFR2), a member of the FGF family with a critical role in pituitary development, in human pituitary tumors has been associated with gene promoter methylation (Zhu et al 2007).…”
Section: Hereditary Endocrine Tumorssupporting
confidence: 80%
“…Interestingly, genes of the RB1 pathway were methylated in 85% of the samples, which suggests that, in addition to MEN1 mutations, methylation could be a molecular alteration that contributes to these tumors. These results were also confirmed by Bello et al (2006), who found promoter hypermethylation in the RB1, P14 (ARF), P16, and P73 genes, as well as the metalloproteinase inhibitor 3 (TIMP3), O-6-methylguanine DNA methyltransferase (MGMT), DAPK (DAPK1), THBS1, and CASP8 genes, some of which are involved in the apoptosis processes (DAPK and CASP8), DNA repair (MGMT) or have anti-angiogenic properties (THBS1). Additionally, reduced expression of the fibroblast growth factor receptor (FGFR2), a member of the FGF family with a critical role in pituitary development, in human pituitary tumors has been associated with gene promoter methylation (Zhu et al 2007).…”
Section: Hereditary Endocrine Tumorssupporting
confidence: 80%
“…Several studies have evaluated MGMT expression status by immunohistochemistry and/or methylationspecific PCR in pituitary adenomas (11,23,24). However, to our knowledge, this is the first report of immunohistochemical analysis of MGMT expression in corticotroph tumors from patients with Cushing's disease in which a large number of tumor samples was classified according to histologic types.…”
Section: Discussionmentioning
confidence: 99%
“…No significant correlation was found with methylation values and age groups by non-parametric Wilcoxon testing. 6,8,[11][12][13][14][15][16][17][18] Among these 19 genes, PAK3, NISCH and KIF1A were previously only tested in a small set of thyroid cancer samples by our group as a part of our comprehensive approach to discover methylated genes in cancer. 8 Three of the 22 genes, MINT1, DCC and AIM1, have not been tested in thyroid cancer to date.…”
Section: Resultsmentioning
confidence: 99%